Implementações computacionais e aplicação no estudo de ligações químicas em metais hexacarbonil isoeletrônicos - Santos Junior, Carlos Vital dos (2019)
The chemical bonds, defined as interactions between two atoms, are phenomena not easily accessible experimentally. Therefore, computational chemistry methods have been developed and applied for the analysis of these interactions in different kind of systems. The Chemical Bond Overlap Software (ChemBOS) is a computer program that uses localized molecular orbitals to do chemical bond analysis calculating overlap properties for general molecular systems. Like most of the programs in the area, ChemBOS presents high computational demand. The common strategy to decrease the processes computational time is to use parallel computation with good load balance. Besides that, to show the applicability of an methodology is an important step in its development, and to apply the methodology for a series of systems with a systematic variation of known properties is an way to test the efficiency of the model. The chosen system in this work is the hexacarbonyl series of type [M(CO)6]n, for which the retrodonation effect can be identified in experimental data. The aim of this work is to compare different parallel strategies in the numerical integration at ChemBOS, comparing the accuracy, precision and execution performance in parallel. Also, this work aims to apply the overlap model to study hexacarbonyl organometallic systems, in comparison with experimental data and QTAIM model. To do the implementation, it was applied different strategies of numerical integration at ChemBOS and performance tests based on speedups were done in function of threads numbers. At the organometallic chemical bonds study, frequency calculations, overlap properties and QTAIM analysis were done. The strategy introduced by this work, here called “malleable subspace” showed better performance regarding the parallel computation, keeping a numerical precision in a range near the Adaptive Monte Carlo. The obtained results using the overlap model to the organometallic systems reveal a high sensibility to the retrodonation effect, being sensitive to the increase of CO stability in function of the increase of the nuclear charge of the metal in a isoelectronic series. These results corroborate the trend observed for the CO stretching frequencies. Therefore, it should be noted that the overlap model provides confident results, that are coherent with the experimental data and with other theoretical tools.